2011
DOI: 10.3397/1.3528970
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vegetation on reducing traffic noise from a city ring road

Abstract: This study was designed to investigate the reduction of road noise by vegetation along the ring road of Thessaloniki. Road noise was measured at two sites, one through a belt of trees and the other on a grass-covered ground. A total of 245 measurements were taken from each site over a two-month period and expressed as differences in L Aeq . Also measurements of the number of vehicles per minute, the type of vehicles and analytic description of vegetation were taken at both sites. The results showed higher nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 9 publications
1
21
0
3
Order By: Relevance
“…Aylor [3] confirmed that corn crop reduced noise propagation by 5 to 6 dB. This is similar to that of Samara et al [4] who concluded that a Pinus brutia belt of trees reduced traffic noise by 6 dB. Bernatzky [5] marked that greater noise attenuation of 12 dB was offered by parks.…”
Section: Introductionsupporting
confidence: 77%
“…Aylor [3] confirmed that corn crop reduced noise propagation by 5 to 6 dB. This is similar to that of Samara et al [4] who concluded that a Pinus brutia belt of trees reduced traffic noise by 6 dB. Bernatzky [5] marked that greater noise attenuation of 12 dB was offered by parks.…”
Section: Introductionsupporting
confidence: 77%
“…Exposure to natural environments appears to stimulate healing and reduce stress [ 1 , 2 , 3 , 4 ]. Additional research in the U.S. and Europe indicate that urban greenspaces also provide opportunities for physical activity and social interaction while vegetation reduces exposure to noise [ 5 , 6 ], air pollution [ 7 , 8 , 9 ], and extreme heat [ 10 , 11 ]. Recent studies and reviews have found evidence that neighborhood greenness is associated with higher levels of physical activity, better mental health outcomes, less cardiovascular disease, increased birthweight, and decreased mortality [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urban trees provide several environmental amenities (Givoni 1991), including shade on hot days (Scott et al 1999), reductions in wastewater loads on treatment facilities (Keim et al 2006), and reduced air pollution (Hwang et al 2011; Nowak 1994) and noise pollution (Samara and Tsitsoni 2011) from vehicular traffic. Research also suggests that urban trees are associated with reduced all-cause mortality after adjustment for neighborhood deprivation (Mitchell et al 2011), and green spaces are associated with many positive health outcomes (Lee and Maheswaran 2010), including improved pregnancy outcomes (Dadvand et al 2012).…”
mentioning
confidence: 99%